MUC5B rs35705950 minor allele associates with older age and better survival in idiopathic pulmonary fibrosis - van der Vis, Joanne J; Prasse, Antje; Renzoni, Elisabetta A; Stock, Carmel J W; Caliskan, Canay; Maher, Toby M; Bonella, Francesco; Borie, Raphael; Crestani, Bruno; Petrek, Martin; Wuyts, Wim A; Wind, Anne E; et al. (Respirology, 2023)
BACKGROUND AND OBJECTIVE: The minor T-allele of the MUC5B promoter polymorphism rs35705950 is strongly associated with idiopathic pulmonary fibrosis (IPF). However, conflicting results have been reported on the relationship between the MUC5B minor allele and survival and it is unknown whether a specific subgroup of IPF patients might benefit from MUC5B minor allele carriage. We investigated the association between MUC5B rs35705950, survival and patient characteristics in a real-world population of European IPF patients. METHODS: In this retrospective study, 1751 patients with IPF from 8 European centres were included. MUC5B rs35705950 genotype, demographics, clinical characteristics at diagnosis and survival data were analysed. RESULTS: In a multi-variate Cox proportional hazard model the MUC5B minor allele was a significant independent predictor of survival when adjusted for age, sex, high resolution computed tomography pattern, smoking behaviour and pulmonary function tests in IPF. MUC5B minor allele carriers were significantly older at diagnosis (p = 0.001). The percentage of MUC5B minor allele carriers increased significantly with age from 44% in patients aged <56 year, to 63% in patients aged >75. In IPF patients aged <56, the MUC5B minor allele was not associated with survival. In IPF patients aged ≥56, survival was significantly better for MUC5B minor allele carriers (45 months [CI: 42-49]) compared to non-carriers (29 months [CI: 26-33]; p = 4 × 10-12 ). CONCLUSION: MUC5B minor allele carriage associates with a better median transplant-free survival of 16 months in the European IPF population aged over 56 years. MUC5B genotype status might aid disease prognostication in clinical management of IPF patients.
Keywords: alely; Alleles; retrospektivní studie; lidé; senioři; mucin 5B; Idiopathic Pulmonary Fibrosis; Genotype; genotyp; Aged; idiopatická plicní fibróza; Retrospective Studies; Polymorphism, Genetic; genetická predispozice k nemoci; polymorfismus genetický; Genetic Predisposition to Disease; Mucin-5B; Humans